Erbium-doped fiber amplifiers fundamentals and technology - Becker, P. C.; Olsson, N. A.; Simpson, J. R. (Jay R.) (San Diego : Academic Press, 1999)
Erbium Fiber Amplifiers is a comprehensive introduction to the increasingly important topic of optical amplification. Written by three Bell Labs pioneers, the book stresses the importance of the interrelation of materials properties, optical properties, and systems aspects of optical fiber amplifiers. The floppy disk included with the book contains a PC based educational version of the sophisticated commercial amplifier simulation package OASIX (sold by the Specialty Fiber Group of Lucent Technologies). This powerful numerical simulation software allows one to simulate the performance of a real erbium fiber amplifier, and obtain its properties such as signal gain and noise generated. Several parameter sets are included, each of which represents a commercially available type of erbium doped fiber usedin different kinds of amplifiers (e.g. preamplifiers and power amplifiers). The user can vary, via Windows based input screens, various amplifier characteristics such as fiber length, pump power, signal power, and additional signals. The output is savedin a file which can be read by any spreadsheet or plotting package for graphical representation of the results. The software allows the reader to explore on his or her own the concepts of amplifier performance discussed in the book, and gain a more intuitive and interactive educational experience leading to a richer understanding of erbium-doped fiber amplifiers and their applications. Key Features * Includes a software disk with a PC-based amplifier simulation tool derived from a sophisticated commercial package (OASIX), which allows the reader to gain an interactive educational experience using parameters for commercially available erbium-doped fibers * Explains the theory of noise in optically amplified systems in an intuitive way * The book contains a discussion of components used in amplifier fabrication and of the attendant technologies used in real systems * The book provides basic tools for amplifier design as well as systems engineering, including the latest developments in WDM and soliton systems * The book discusses the fundamentals of rare earth ions for the reader desiring more depth in the topic * The book is for either the novice of experienced reader * The chapter have links between them to allow the reader to understand the relationship between the amplifier characteristics, noise, and systems applications * The book contains extensive references.
INTRODUCTION -- 1.1 Long Haul Fiber Networks -- 1.2 Historical Development of Erbium-Doped Fiber Amplifiers -- 1.3 From Glass to Systems -- 2 OPTICAL FIBER FABRICATION -- 2.1 Introduction -- 2.2 Conventional Communication Fiber -- 2.3 Rare Earth Doped Fibers -- 2.4 Pump-Signal Interaction Methods -- 2.5 Compositions -- 2.6 Physical Properties -- 3 COMPONENTS AND INTEGRATION -- 3.1 Introduction -- 3.2 Fiber Connectors -- 3.3 Fusion Splicing -- 3.4 Pump and Signal Combiners -- 3.5 Isolators -- 3.6 Circulators -- 3.7 Filters -- 3.8 Fiber Gratings -- 3.9 Signal Multiplexers and Demultiplexers -- 3.10 Signal Add/Drop Components -- 3.11 Dispersion Compensation Components -- 3.12 Integrated Components -- 3.13 Pump Lasers -- 4 RARE EARTH IONS--INTRODUCTORY SURVEY -- 4.1 Introduction -- 4.2 Atomic Physics of the Rare Earths -- 4.3 Optical Spectra of Rare Earth Ions -- 4.4 Fundamental Properties -- 4.5 Spectroscopy of the Er3 Ion -- 4.6 Er3 -Er3 Interaction Effects -- 5 ERBIUM-DOPED FIBER AMPLIFIERS--AMPLIFIER BASICS -- 5.1 Introduction -- 5.2 Amplification in Three-Level Systems -- 5.3 Reduction of the Three-Level System to the Two-Level System -- 5.4 Amplified Spontaneous Emission -- 5.5 Analytical Solutions to the Two-Level System -- 6 ERBIUM-DOPED FIBER AMPLIFIERS--MODELING AND COMPLEX EFFECTS -- 6.1 Introduction -- 6.2 Absorption and Emission Cross Sections -- 6.3 Gain and ASE Modeling -- 6.4 Amplifier Simulations -- 6.5 Transverse Mode Models--Erbium Confinement Effect -- 6.6 Excited State Absorption Effects -- 6.7 Er3 -Er3 Interaction Effects -- 7 OPTICAL AMPLIFIERS IN FIBER OPTIC COMMUNICATION SYSTEMS--THEORY -- 7.1 Introduction -- 7.2 Optical Noise: Device Aspects -- 7.3 Optical Noise: System Aspects -- 8 AMPLIFIER CHARACTERIZATION AND DESIGN ISSUES -- 8.1 Introduction -- 8.2 Basic Amplifier Measurement Techniques -- 8.3 Amplifier Design Issues -- 9 SYSTEM IMPLEMENTATIONS OF AMPLIFIERS -- 9.1 Introduction -- 9.2 System Demonstrations and Issues -- 9.3 Soliton Systems -- 10 FOUR LEVEL FIBER AMPLIFIERS FOR 13 MM AMPLIFICATION -- 10.1 Introduction -- 10.2 Pr3 -doped Fiber Amplifiers -- 10.3 Nd3 -doped Fiber Amplifiers -- Appendix -- Subject Index.
Includes bibliographical references and index.
Keywords: Optical communications -- Equipment and supplies; Optical amplifiers; Optical fibers; Electronic books